Análisis del cumplimiento tributarío para una empresa de servicio publicitarios ubicada en la ciudad de Guayaquil para el período fiscal 2007 - Vera Carrera, Sandra Matilde (2009)
The Tributary Audit is important to prove that the company to be reflected correct the tax obligations, agreed to pay in the time and requirement to be reflected for law. The tributary Audit was designed for a companies to market service, beginning with an analysis of the company for to know situation and to decide the article necessary the law, regulation and tributary code valid in the own country in the time 2007 and beginning 2008. Then to determined value, customers, action lines and standard that to obtain the voluntary form by to offer better service, and finally determine sales, buys, tax generation, tax retain and analysis statistics. Finally to planed and execute the audit with methodology, proofs and a program the audit that can to serve for to emit recommendation with the responsibility tributary.